2006
DOI: 10.1136/jcp.2004.023135
|View full text |Cite
|
Sign up to set email alerts
|

The ECM proteoglycan decorin links desmoplasia and inflammation in chronic pancreatitis

Abstract: Decorin is a molecular marker of desmoplasia in CP, and excessive decorin may allow fibrotic masses to nourish and protract inflammation by deregulating the process of MNC accumulation and activation. These data provide a molecular basis for surgical resection of diseased tissue as a treatment option in CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Simulations of the model indicated that TNF-α, TGF-β, IL-6, and PDGF are likely to increase in the pancreatic microenvironment during chronic pancreatitis. These results are consistent with those observed from prior clinical data (46)(47)(48)(49). The model can be used to explore, in silico, the efficacy of treatments that target some of the overexpressed cytokines.…”
Section: Discussionsupporting
confidence: 83%
“…Simulations of the model indicated that TNF-α, TGF-β, IL-6, and PDGF are likely to increase in the pancreatic microenvironment during chronic pancreatitis. These results are consistent with those observed from prior clinical data (46)(47)(48)(49). The model can be used to explore, in silico, the efficacy of treatments that target some of the overexpressed cytokines.…”
Section: Discussionsupporting
confidence: 83%
“…[33][34][35][36] It is therefore noteworthy that decorin has been shown to act as a proinflammatory factor and is produced at sites of inflammation. 18,[37][38][39][40][41] In contrast, Decorin, obesity and type 2 diabetes K Bolton et al decorin has also been reported to bind and inhibit the proinflammatory activity of the complement protein C1q 42 and has been hypothesized to antagonize C1q-induced insulin resistance in adipose tissue that is associated with obesity. 16 These observations indicate that decorin may play a role in inflammation associated with obesity in adipose tissue; however, this is likely to be a complex interaction between pro-and anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 99%
“…Standard markers which stain CP and PDAC stroma include the intracellular marker a-SMA and the ECM components such as collagen I, collagen III, decorin, tenascin, and fibronectin. A series of expression profiling studies of PDAC have collectively identified a lengthy list of genes upregulated not only in PDAC stroma but also in CP stroma as well [Crnogorac-Jurcevic et al, 2001;Binkley et al, 2004;Sato et al, 2004;Shen et al, 2004;Fukushima et al, 2005;Esposito et al, 2006;Koninger et al, 2006]. Indeed, serum biomarker studies for tumor routinely use CP for controls [Koopmann et al, 2006].…”
Section: Formation Of Pdac Stroma (I): Fibroblasts and Other Mesenchymentioning
confidence: 96%